Policing in a changing Vietnam : towards a global account of policing - Jardine, Melissa (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2023)
Knowledge about policing has been produced and disseminated unevenly so that our understanding comes from a skewed emphasis on the Anglo-American experience. Drawing on an original and comprehensive study of policing in Vietnam and engaging a Southern Criminological framework, this book explores police cultures and practices in a postcolonial, post-Confucian, transitioning economy. Identifying both similarities and differences in policing and police culture in Vietnam with those found in the dominant literature from the Global North, Policing in a Changing Vietnam challenges assumptions that police are (purportedly) apolitical, averse to tertiary education and defer to legalistic approaches to policing and law enforcement. It highlights that the variations identified in policing in Vietnam must be understood, not as deviations from Anglo-American normality, but as significant separate practices and traditions of policing from which the Global North may have something to learn. Contributing to ongoing debates on police culture and socialisation, this book explores the assumptions about relationships between the police, political systems, broad societal cultures, legal frameworks, organisations, communities and gender. An accessible and compelling read, this book will appeal to students and scholars of criminology, policing, gender studies, sociology, politics, law and all those who are interested in understanding the experiences and views of the Vietnamese police.
Keywords: Police -- Vietnam; Criminal justice administration -- Vietnam; POLITICAL SCIENCE / Political Freedom & Security / Law Enforcement; SOCIAL SCIENCE / Criminology